Prognostic value of brain injury biomarkers in acute encephalitis/encephalopathy. Issue 4 (10th June 2013) - Tsukahara, Hirokazu; Fujii, Yosuke; Matsubara, Kousaku; Yamada, Mutsuko; Nagaoka, Yoshiharu; Saito, Yukie; Yashiro, Masato; Tsuge, Mitsuru; Goto, Shinichiro; Kitamura, Tetsuro; Hata, Atsuko; Ichiyama, Takashi; et al.
Abstract: Background: Acute encephalitis/encephalopathy (AEE) is a devastating cause of severe neurodevelopmental sequelae or death in children. Assessing ongoing brain injury and predicting outcomes using bedside point‐of‐care testing is expected to be extremely valuable. Methods: For this study, three brain injury markers, S‐100B, glial fibrillary acidic protein (GFAP), and tau protein, were measured in early cerebrospinal fluid samples of children with AEE. Subjects comprised three groups: Group 1 (non‐AEE control, n = 27); Group 2 (AEE with normal resolution or mild sequelae, n = 13); and Group 3 (AEE with severe sequelae or death, i.e. "poor outcome, " n = 10). Results: All marker levels were significantly higher in Group 3 than in Group 1 or 2. In Group 3, only S‐100B was significantly higher in non‐survivors than in survivors. For scoring assessment (range: 0–3 points), the predictive accuracies of 3 points for poor outcomes in children with AEE (i.e. Group 2 and 3, n = 23) were 91% (21/23) for S‐100B, 74% (17/23) for GFAP, and 78% (18/23) for tau. When the scores were summed up for S‐100B, GFAP, and tau (range: 0–9 points), and for S‐100B and tau (range: 0–6 points), the patients with poor outcomes were identified more accurately using the respective thresholds of 6 points and 4 points (96% [22/23] and 100% [23/23], respectively). Conclusion: Our findings suggest that combined measurement and scoring assessment of the markers, especially S‐100B and tau, show promise as predictors of clinical outcomes in children with AEE.